THE ANALYSIS OF TEACHER TALK AND CHARACTERISTIC OF CLASSROOM INTERACTION IN ENGLISH AS A FOREIGN LANGUAGE CLASSROOM - Putri, Dina Septryana (2015)
The paper entitled "The Analysis of Teacher Talk and Characteristics of Classroom Interaction in English as a Foreign Language Classroom" is aimed at analyzing the categories of teacher talk found in the classroom and characteristics of interaction that occurred in teaching and learning process based on the views that teacher talk is an important part in the classroom and has effect on students-teacher interaction. Hence, this study presents an analysis of type of teacher talk and characteristic of classroom interaction in English as a foreign language class based on Flanders' Interaction Analysis Categories that consists of indirect and direct influence of teacher, students' initiation and responds, and silent moment. This study was categorized as a case study because of its limited number of individuals and the absence of treatment. The categories of teacher talk and interaction characteristics were found by employing classroom observation with the help of video recording. The study also looked for the students' opinion in the classroom toward their teacher talk by using questionnaire. In the study, it was found that all the categories of teacher talk in FIAC appeared in the classroom. However, asking questions and lecturing were in dominance. This was in line with the opinion from students that their teacher was likely to ask many questions to them. The characteristics of classroom interaction were also found in teaching and learning process with the dominant one is content cross (asking and lecturing). Therefore it can be concluded that categories of teacher talk could affect the characteristics of interaction in the classroom. ------------ Skripsi yang berjudul "The Analysis of Teacher Talk and Characteristics of Classroom Interaction in English as a Foreign Language Classroom" bertujuan untuk menganalisa kategori-kategori bahasa guru yang ada di kelas dan ciri interaksi kelas yang muncul dalam proses belajar mengajar berdasarkan pandangan bahwa bahasa guru merupakan hal yang penting dalam kelas dan memiliki pengaruh pada interaksi guru-siswa. Oleh karena itu, studi ini menyajikan analisa tipe bahasa guru dan karakteristik interaksi kelas dalam kelas bahasa Inggris sebagai bahasa asing mengacu pada Kategori Analisis Interaksi Flanders yang terdiri dari pengaruh guru secara tidak langsung dan langsung, respon dan inisiatif siswa, serta saat diam. Studi ini termasuk dalam studi kasus karena jumlah individu yang terbatas dan ketiadaan pemberian perlakuan. Kategori-kategori bahasa guru dan ciri interaksi ditemukan dengan menggunakan observasi kelas dengan bantuan rekaman video. Penelitian ini juga mencari pendapat siswa di kelas mengenai bahasa guru mereka dengan menggunakan kuesioner. Dalam studi ini, ditemukan bahwa semua kategori bahasa guru dalam Kategori Analisis Interaksi Flanders muncul dalam kelas. Akan tetapi, bertanya dan berceramah merupakan kategori yang paing dominan di antara seluruh kategori. Penemuan ini sesuai dengan pendapat siswa yang mengatakan bahwa guru mereka cenderung memberikan banyak pertanyaan pada mereka. Ciri interaksi kelas juga ditemukan dalam proses belajar mengajar dengan satu ciri yang paling mendominasi yaitu lintas isi (bertanya dan memberi informasi). Oleh karena itu dapat disimpulkan bahwa tipe bahasa guru dapat mempengaruhi ciri interaksi di dalam kelas.